La Llegenda del llibreter assassí de Barcelona . Tradizione e traduzione. Note al margine dell'edizione italiana. - RAVASINI, INéS (Scripta, 2013)
The recent publication of the Italian translation of La llegenda del llibreter assassí by Ramon Miquel i Planas provides an opportunity to make a comparison with some previous Spanish translations and to reflect briefly on translation methods. The two Spanish versions (1991 and 2011), unlike the Italian one, are free reworkings of the original, in the sense that they alter the structure, transform the text and shape it to new ends. What is interesting about this «manipulation» is that it is in some way legitimised by the heterogeneous nature of Miquel i Planas's work, which is both an erudite volume and an anthology of different narrative materials, as well as by the varied ways in which the Catalan scholar handles materials relating to legends. The versions of Llegenda thus permit the inclusion of this reflection on translation in the sphere of the reception of a text and of the influence exerted by the tradition surrounding a text on the ways it is translated.